Sustainable bioelectricity generation using Cladophora sp. as a biocathode in membrane-less microbial fuel cell - Taskan, Banu; Taskan, Ergin (Elsevier Sci Ltd, 2022)
In this study, the Cladophora sp. is used to provide oxygen to the cathode of the photosynthetic biocathode membrane-less microbial fuel cell (PB-MLMFC). Non-aerated (NA-MLMFC) and mechanically-aerated (MA-MLMFC) MLMFCs are operated under similar operating conditions to evaluate the performance of PB-MLMFC with the presence of Cladophora sp. The PB-MLMFC exhibits the highest dissolved oxygen (DO) concentration, which results in a more efficient oxygen reduction reaction and a significant improvement in the electricity generation performance. The maximum power density of PB-MLMFC is 619.1 mW m(-2), which is the highest power density known to be reported for algal cathode MFCs in the literature. The electrochemical analysis shows that the Cladophora sp. reduces the charge (R-ct) and mass transfer (R-mt) resistances of the PB-MLMFC, and improves the bioelectrochemical activity of the anode microorganisms. The study reveals that Cladophora sp. provides a cost-effective and renewable approach for practical applications of MLMFCs.
Keywords: Membrane-less microbial fuel cell; Cladophora sp.; Photosynthetic biocathode; Electricity generation; Microbial community